2007
DOI: 10.1111/j.1365-2672.2007.03431.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological quality of water and dialysate in a haemodialysis unit in Ponta Grossa-PR, Brazil

Abstract: Aims:  The objective of the study was to determine the microbiological quality of samples of water and dialysate in a haemodialysis unit. Methods and Results:  Seventy‐two samples each of water and dialysate were collected during November 2003 to April 2004. The following microbiological analyses were performed: test for total and faecal coliforms, which produced negative results for all the samples; counts of total heterotrophic bacteria, where three samples of water and two of dialysate showed levels higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
18
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 17 publications
(21 reference statements)
3
18
1
2
Order By: Relevance
“…All Pseudomonas isolates in dialysis water were highly resistant to tetracyclines, which have been the most commonly prescribed antibiotics since the 1950s. The same result is reported by other studies [25, 22]. Tetracycline resistance can be mediated by plasmid-encoding genes such as tet genes, which encode a tetracycline efflux system or protect ribosomes from the action of tetracycline [26].…”
Section: Discussionsupporting
confidence: 82%
“…All Pseudomonas isolates in dialysis water were highly resistant to tetracyclines, which have been the most commonly prescribed antibiotics since the 1950s. The same result is reported by other studies [25, 22]. Tetracycline resistance can be mediated by plasmid-encoding genes such as tet genes, which encode a tetracycline efflux system or protect ribosomes from the action of tetracycline [26].…”
Section: Discussionsupporting
confidence: 82%
“…A particular study showed a reduction in the adherence in 500ppm sodium hypochlorite [13]. However, in our study, we did not find any decrease and this may be due to the increased adherence of bacteria as a protective mechanism, to evade the action of chlorine.…”
Section: Discussioncontrasting
confidence: 56%
“…Studies show that approximately 90% of the bacteria isolated in hemodialysis water are Gramnegative. This bacteria multiplies rapidly, reaching concentrations greater than 10 5 CFU/ml in less than 24 hours (Borges et al, 2007). Research has identified that the main microorganisms isolated in hospitals are Staplylococcus aureus, Streptococcus pneumoniae, Enterococcus, Pseudomonas sp, Escherichia coli and Candida albicans.…”
Section: Discussionmentioning
confidence: 99%
“…Improper maintenance of hemodialysis water systems and reprocessing of dialyzers may result in reactions in hemodialysis patients (Borges et al, 2007). The quality of dialysis fluids depends on complex systems with devices and procedures that allow for effective treatment.…”
Section: Discussionmentioning
confidence: 99%